MEMAHAMI KEMBALI TENTANG MAKNA HADIS ORANG TUA NABI MUHAMMAD SAW MASUK NERAKA - Muhammad Sulthon Mardia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The study in this approach uses the study of semantic theory in the methodology of Hadith science, semantics is to analyze the relationships of signs with objects which are the container for the application of these signs. Thus, semantics can be interpreted as the science of meaning or about the meaning of language. This theory was introduced by Charles Morris and Rudolf Carnap. The language used by the Prophet. in its expression about